Brief report: cultural adaptations for the PEERS program for Latine families - Martin, Ann Marie; Blacher, Jan; Veytsman, Elina; Baker, Elizabeth; Fodstad, Jill; Meltzoff, Katherine (Frontiers in Education, 2024)
Background: The UCLA PEERS program has been studied using predominantly White and affluent populations. As autistic teens and their parents are represented across cultures, it is vitally important that interventions are tailored to their needs -whether that be linguistically or with respect to their cultural practices. Thus, the current qualitative study explored whether culturally and linguistically diverse families (primarily Latine) participating in the PEERS program had recommendations for adaptations to improve their experience and make the program more culturally sensitive. Method: The study utilized a sample of 13 autistic teens and their parents who completed the original 16-week PEERS program with content delivered bilingually. Results: All parents and teens recommended the program to other families. Although the intervention was largely accepted in its current format, suggestions were put forth regarding how to adapt the program to be more accommodating of Latine cultural views on parenting. Conclusions: The PEERS program is an evidenced based intervention with well documented positive results. This paper contributes to a growing body of literature highlighting both the importance of including underrepresented demographic groups in research and factoring in cultural adaptations to increase validity of interventions previously normed on White affluent populations.